Autoimmunity Pathogenesis, Clinical Aspects and Therapy of Specific Autoimmune Diseases - Chatzidionysiou, Katerina (IntechOpen, 2015)
Autoimmunity is defined as an immune response against a self-antigen. This abnormal immune response can lead to tissue damage and to the development of autoimmune disease. From organ-specific autoimmune diseases, such as myasthenia gravis, to non-organ-specific, such as systemic lupus erythematosus, autoimmune diseases represent a heterogeneous group of disorders which affect approximately 6% of the population. The pathogenesis of many autoimmune diseases is complex and remains not completely understood. The aim of this book is to present current knowledge regarding pathogenic mechanisms of autoimmune diseases, clinical aspects of specific autoimmune diseases, like vitiligo, celiac disease and autoimmune liver disease, as well as insights regarding specific therapies.